Journey of Mesenchymal Stem Cells for Homing: Strategies to Enhance Efficacy and Safety of Stem Cell Therapy - Sung Keun Kang; Il Seob Shin; Myung Soon Ko; Jung Youn Jo; Jeong Chan Ra (Stem Cells International)
Human mesenchymal stem cells (MSCs) communicate with other cells in the human body and appear to “home” to areas of injury in response to signals of cellular damage, known as homing signals. This review of the state of current research on homing of MSCs suggests that favorable cellular conditions and the in vivo environment facilitate and are required for the migration of MSCs to the site of insult or injury in vivo. We review the current understanding of MSC migration and discuss strategies for enhancing both the environmental and cellular conditions that give rise to effective homing of MSCs. This may allow MSCs to quickly find and migrate to injured tissues, where they may best exert clinical benefits resulting from improved homing and the presence of increased numbers of MSCs.